2022
DOI: 10.24868/10703
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Future of Maritime Autonomy: Cybersecurity, Trust and Mariner’s Situational Awareness

Abstract: As technology evolves, the level of automation in the maritime industry grows, and will continue to grow significantly, as the industry strives for fully autonomous vessels. Current maritime operations on board rely on a mixture of automated processes, human decision making, and human interventions. In the future autonomy may lead to the removal of the mariner physically on board, increasing remotely operated vessels. The remote nature of these operations will subject mariners to new operational risks, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This could be of interest to evaluate if the level of training the crew receives is adequate when considering cyber-physical threats. Other studies on crew perception of cyber-risk can be found in Larsen and Lund (2021b) and Misas et al (2022).…”
Section: Discussionmentioning
confidence: 99%
“…This could be of interest to evaluate if the level of training the crew receives is adequate when considering cyber-physical threats. Other studies on crew perception of cyber-risk can be found in Larsen and Lund (2021b) and Misas et al (2022).…”
Section: Discussionmentioning
confidence: 99%
“…Misas et al's survey [97] identifies five key challenges for the future of maritime autonomy, including low cyber awareness in the industry, leading to potential over-reliance on digital tools, the need for regulatory adaptation to the evolving cyber threat landscape, as well as concerns that critical decisions will be influenced by inaccurate data or mistrust in accurate systems, the reduction of over-reliance on digital tools, and the potential obstruction of operators' security controls due to their physical separation from the ship. They emphasize the importance of equipping long-distance mariners with the necessary knowledge and skills, particularly in the use of digital systems, and highlight the need for future training of seafarers to meet the evolving challenges and incorporate new skills such as communication and multi-ship management.…”
Section: Surveys and Studies Of Collaboration Between Industry Stakeh...mentioning
confidence: 99%